Advances in Liquid‐Phase and Intercalation Exfoliations of Transition Metal Dichalcogenides to Produce 2D Framework. Issue 14 (21st June 2021) - Raza, Ali; Hassan, Jahan Zeb; Ikram, Muhammad; Ali, Salamat; Farooq, Umer; Khan, Qasim; Maqbool, Muhammad
Abstract: A host of innovative developments in technology have led by 2D materials owing to their remarkable electronic and physical properties which opens doors for advanced research areas and horizons of material science. Among these materials, transitional metal dichalcogenides (TMDCs) e.g., MoS2, WS2, MoSe2, and WSe2, are reflected as promising candidates of 2D family. Despite significant achievements, the primary challenge is to produce these 2D materials with high purity, massive yield, and well‐controlled structure that lead to fundamental research as well as industrial applications in an efficient and scalable way. A variety of techniques have been employed to develop 2D‐TMDCs, such as mechanical exfoliation, chemical vapor deposition, and chemical exfoliations. Among state‐of‐the‐art synthetic protocols, chemical exfoliations including Liquid‐phase and intercalation isolations of TMDCs are deliberated as promising solutions for high yield, great performance, low cost, and excellent up‐scalability. Herein, a succinct and comprehensive survey of recent progress in chemical exfoliation routes is presented with the processing techniques, strategic design for exfoliations, and mechanisms of individual approaches. The focus of this review is to fulfill the gap in recent reviews such as underlying mechanisms, chemistries, and critical hurdles with effective solutions in performing chemical exfoliations and suggesting a framework for future studies of TMDCs' advanced applications. Abstract : Large‐scale transitional metal dichalcogenides (TMDCs) development is a crucial challenge in the horizons of materials science; this review provides suitable routes to commercialize TMDCs. The dynamics and chemistry of liquid‐phase exfoliation provide ease of scaling‐up and suitability for various applications with authors' remarks. Finally, insight on challenges posed by exfoliated TMDCs and their possible solutions with authors' recommendations for future opportunities are provided.